RESEARCH ON CREEP TEST AND CONSTITUTIVE MODEL COMPARISON OF COMРАСTED GRAPHITE CAST IRON UNDER WIDE TEMPERATURE AND STRESS RANGE - LI ShuBo; LIU Qian; JING GuoXi; ZHANG JunHai; WEI JunChao; YANG ZiYi; SUN Shuai (Jixie qiangdu)
As the power density of an engine increases, so does the temperature and stress that the cylinder head is subjected to during operation. Therefore, creep damage prediction needs to consider accurate creep constitutive models and parameters. Aiming at the wide range of temperature and stress working conditions of the compacted graphite cast iron (CGI) cylinder head, CGI creep test was carried out at 450-550 °C and 100-300 MPa. The comparative study of creep constitutive models to characterize the minimum creep rate of CGI under a wide range of temperature and stress was carried out. The research shows that compared with a smaller range of temperature and stress, CGI is more prone to creep damage under wide conditions. and temperature can promote the creep deformation of CGI more than stress. Based on the Norton-Bailey power law model, the Garofalo hyperbolic sine model, and the deformation mechanism-based true stress (DMTS) model respectively, combined with the multi-objective optimization method, the CGI creep constitutive model was constructed. Among them, 73% of the predicted values of the CGI creep model based on the DMTS model are within twice the error range, and the coincidence effect is the best among the three models.